Help Me Where I Am: Scaffolding Writing in Preschool Classrooms. (2nd August 2016) - Quinn, Margaret F.; Gerde, Hope K.; Bingham, Gary E.
Abstract: Early writing is important to young children's development—research indicates that writing is predictive of later reading and writing. Despite this, preschool teachers often do not focus on writing and offer limited scaffolding to foster children's writing development. This article shares innovative ways to scaffold early writing across the three component skills of writing: composing, spelling, and forming letters.